Safety and effectiveness of electronic cigarette as vapers perspective: a qualitative approach - ., Aziz-ur-Rahman; Nik Mohamed, Mohamad Haniki; Jamshed, Shazia Qasim (Japan International Cultural Exchange Foundation (JICEF), 2015)
Objective: To determine the effectiveness, safety, and to explore opinion towards electronic cigarette among Malaysian vapers. Design: A qualitative method was adopted to gain deeper understanding about vaping from e-cig user's point of view ((also called vapers). Twelve vapers from Kuantan and Pekan districts of Pahang state, Malaysia were interviewed using a semi-structured interview guide. Open ended questions were asked and all participants given full liberty to express views about e-cigs. Results: Seven themes developed that defined users opinion about e-cigs.l)As quit smoking aid 2) To decline consumption of tobacco cigarettes 3) Alternative device to take nicotine 4) To reduce cost of smoking 5) As healthier alternative to smoking 6) To manage withdrawal symptoms 7)More enjoyable compare to other tobacco products. Conclusion: The above finding suggests that, at least anecdotally, these are the elements that seem to assist Malaysian existing vapers to self-restraint from smoking.